America at play, america at war: the super bowl as discursive formation - O’Donnell, Hugh (2020)
This article analyses the last ten Super Bowls (1999-2008) and the image they present of America as a society characterised by fun, opportunity and enterprise, all carried out under the protection of the state and military. It addresses the troublesome place of both race and gender within this configuration, and pays particular attention to the changes which took place in the aftermath of the September 11 attacks responding to the motif of «America at war», changes which would themselves be affected by the gradual loss of social support for the war in Iraq.